The Writing of Anxiety - Stonebridge, L. author. aut Link
X, 173 p.
Keywords: This study suggests that it was the representation of anxiety, rather than trauma and memory, that emerged most forcefully in mid-century wartime culture. Thinking about anxiety, Lyndsey Stonebridge argues, was a way of imagining how it might be possible to stay within a history that frequently undermined a sense of self and agency.